71 Adrenal Insufficiency among Children treated with Hormonal Therapy for Infantile Spasms. (29th October 2021) - Doré-Brabant, Gabrielle; Laflamme, Geneviève; Millette, Maude; Chrestian, Nicolas; Osterman, Bradley
Abstract: Primary Subject area: Endocrinology and Metabolism Background: Hormonal therapy is a standard treatment for children with infantile spasms. However, the high doses given and long treatment duration exposes patients to the potential risk of adrenal insufficiency (AI). There is, presently, limited data on occurrence of AI after hormonal therapy in this population. Objectives: This study aims to quantify the incidence of AI among children with infantile spasms treated with high-dose corticosteroids and/or adrenocorticotropic hormone (ACTH). Design/Methods: A retrospective chart review of patients less than 2 years old treated for infantile spasms was performed between January 2009 to March 2020 in one pediatric specialized hospital. Variables collected included sex, age, etiology, age at treatment initiation, type of hormonal treatment, dose and duration of treatment, concomitant medication and illness, other corticosteroid uses, hydrocortisone replacement therapy use, adrenal function testing, and signs of AI. Analysis included descriptive statistics, such as incidence and bivariate analysis. Results: Thirty-one patients met the inclusion criteria and received a total of 33 separated courses of hormonal treatment. Adrenal function following each course of treatment was evaluated in all patients, either by tests or by the presence of adrenal crisis. Oral hydrocortisone replacement therapy was received by 32/33 (97%) children. AI occurred in 25/33 (76% [95% CI 58-89]) children. There was no predictive factor for adrenal insufficiency after hormonal treatment, and no drug regimen (duration or total received dose) was safe. Two patients (6%) presented to the emergency room with an acute adrenal crisis the day following the weaning off of hormonal treatment. They were the youngest children of the cohort, with an age of 1, 6 and 2, 7 months at the initiation of treatment. All other patients were aged 4 months and older. Conclusion: This study suggests that adrenal suppression is frequent after standard hormonal therapy regimen for infantile spasms. This can lead to serious complications, such as adrenal crisis, if not supplemented. A routine laboratory assessment of adrenal function should be done after hormonal therapy for all patients. We suggest that hydrocortisone replacement therapy should be given at the end of hormonal therapy and until testing results for adrenal function are obtained, particularly for younger patients.